Ortega Facing a Young People - Gutiérrez Simón, Rodolfo (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This paper analyses Ortega y Gasset’s, from a general point of view the way in which Ortega y Gasset’s conception of America takes part in his philosophy. In order to do so, firstly, Ortega y Gasset’s Liberalism, Perspectivism and its consequences will be revised. Finally, Ortega y Gasset’s concept of “Youth” will be undertaken, specifically considering its positive and negative meanings that are used by the author to characterize American people. That characterization is both a limit and a possibility for the American continent.
Keywords: Ortega y Gasset; America; Youth; Liberalism; Perspectivism.